(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
The material presented is in the form of conceptual training principles, training loading norms, and training periodization that can be implemented in the training-training process. The principles of practice and described are part of the science that underlies provisions or rules (laws) in practice theory and methodology as stated by William H. Freeman in his book entitled "Peak When it Counts". The division of scientific legal basis includes; physiological law (law of physiological) which consists of the law of overload (law of overload); law of specificity; and the law of reversibility (law of reciprocity). The law of overload includes both the principle of individual training and the principle of overall development. The law of specificity includes the principle of specialization and the principle of the training process model. The law of reciprocity (reversibility) includes the principle of increasing demands, the principle of continuing burden demands, the principle of possibility of occurring easily/feasibility, the principle of recovery or restoration, and the principle of active rest. Psychological law (law of psychological) which consists of: the principle of awareness (awareness), the principle of variation (variety), the principle of psychological rest (psychological rest). Pedagogic laws include; principles of system planning and utilization (planing and use of system); principles of visual presentation (visual presentation); and the principle of periodization (periodization). Another topic that was conveyed in line with and closely related to the principles of training is about training norms which are training rules or rules that cannot be violated. The training loading norms in question are training volume, training intensity, training rest, and also training density. Furthermore, it discusses the definitive periodization of training and its distribution and also training models that suit the needs and demands of athletes to excel at their respective levels. The central issue in the discussion is of course related to the role of nutrition in supporting athlete achievement in each sport, numbers in sports, and also the individual characteristics of athletes at each stage of training and also training needs from aspects of training (technique, physics, tactics, and mental) that is being executed.